Capturing nuisance urban Canada geese using the bird immobilizing agent alpha-chloralose in Reno, Nevada: What we learned - Smith, Mike A. (eScholarship, University of California, 2004)
This paper discusses several challenges Wildlife Services (WS) personnel encountered while conducting alpha-chloralose (AC) treatments on Canada geese in Reno, Nevada during May and June 2003. While the WS AC training manual provides guidelines for the safe and effective anesthetization of Canada geese using this chemical immobilization tool, we encountered and solved problems and challenges that had not been reported in previous reports on projects using AC. Problems we encountered ranged from being accosted by drunks to interrogations by “elderly ladies” worried that we might be taking their favorite goose. Challenges in collecting immobilized geese resulted from river currents and their effect on AC-treated geese, moss entangling the boat motor propeller on ponds, and automatic sprinklers turning on at inopportune times. It is hoped that addressing these real-world experiences can help others become more proficient in AC field use.